2017
DOI: 10.4293/jsls.2017.00041
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Fibroid Management: Systematic Review of the Literature

Abstract: Background and Objectives:Symptomatic uterine fibroids are a societal and healthcare burden with no clear consensus among medical professionals as to which procedural treatment is most appropriate for each symptomatic patient. Our purpose was to determine whether recommendations can be made regarding best practice based on review and analysis of the literature since 2006.Database:A systematic search of journal articles relevant to the treatment of symptomatic uterine fibroids was performed within PubMed, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 68 publications
(37 reference statements)
3
29
0
8
Order By: Relevance
“…These findings are also confirmed by a recent systematic review of the literature [29] reporting high effectiveness of miniinvasive uterine fibroids treatments. Moreover RF ablation showed higher performances if compared to UAE [10] and also a lower re-intervention rate compared to MRg-FUS [30].…”
Section: Discussionsupporting
confidence: 74%
“…These findings are also confirmed by a recent systematic review of the literature [29] reporting high effectiveness of miniinvasive uterine fibroids treatments. Moreover RF ablation showed higher performances if compared to UAE [10] and also a lower re-intervention rate compared to MRg-FUS [30].…”
Section: Discussionsupporting
confidence: 74%
“…Safety of UPA was well established before the present study, [1][2][3][4] and was confirmed as a result of this trial. Although some serious adverse events were reported, these were within the range of the previous trials with UPA.…”
supporting
confidence: 80%
“…Not all fibroids warrant a surgical approach, and surgical treatment of fibroids can be challenging as the more invasive procedures hold a greater risk of complications . Hysteroscopic myomectomy is generally safer than a laparoscopic or even laparotomic approach, but is of course limited to fibroids in conjunction with the uterine cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Міома матки на сьогоднішній день є одні-єю з найбільш розповсюджених патологій жіночої репродуктивної системи [10,14]. Частота захворю-вання варіюється за одними джерелами у 20-25% жінок репродуктивного віку [5], за іншими -від 40 до 60% [13].…”
Section: Farmakod@ukrnetunclassified